Pembagian Masker dan Penyuluhan Mengenai Tanaman Obat Keluarga Di Desa Bila, Kecamatan Sabbangparu, Kabupaten Wajo - Wahyuni Eka Putri (Universitas Hasanuddin, 2021)
The Indonesian Ministry of Health instructs the implementation of Covid-19 prevention efforts as recommended by the World Health Organization. However, there are still many people, especially the people of Bila Village, Sabbangparu District, Wajo Regency, who do not pay much attention to the health program, especially the use of masks when doing activities outside the home and are still lacking in using family medicine as traditional medicine. For this reason, masks were distributed and counseling on family medicinal plants to prevent Covid-19. This work program was carried out on Thursday, December 17, 2020 in one of the houses of the Bila Village community by distributing 10 masks per person as well as providing counseling on planting and using family medicinal plants as prevention of Covid-19 in the form of power points using an LCD. The presentation of this material was carried out with the midwife at Puskesmas Liu, Sabbangparu District, Wajo Regency. From the results of the implementation of this work program, it is hoped that the community will get a change in awareness of the importance of using masks and the skills to plant and utilize family medicinal plants in terms of increasing body immunity to avoid exposure to Covid-19.